Activating the modern classroom - Reed, Julian A.; Weaver-Spencer, Jennifer (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
From the team that brought you Walkabouts - Activating the Modern Classroom presents research and provides engaging, easy-to-implement classroom activities to help elementary-grade teachers address some of today's most pressing challenges. Learn strategies and the science behind them, to activate educational content with movement in ways that improve behavior, increase focus, and enhance academic engagement and performance.Activating the Modern Classroom includes practical tips for elementary-grade teachers to address pressing classroom challenges. In the book, teachers will learn strategies, and the science behind them, to activate language arts, literacy, math, social studies, and science curriculum in ways that improve student behavior, increase student focus, and enhance student' academic engagement and performance. Ideas for incorporating creative movement into the school day (including activity breaks) are also included.Activating the Modern Classroom includes research-based answers to the following questions: What does current brain research tell us about movement? What are activity breaks? and What is an integrated curriculum? In addition, the book includes research-based strategies for helping kinesthetic learners and describes how moving while learning can help students with ADD and ADHD. The book also includes descriptions of three web-based platforms that can be used in the classroom to integrate curriculum and movement and why and how this is beneficial to students. Finally, the book includes movement-based activities for language arts, literacy, math, social studies, and science that integrate movement and improve student behavior, increase student focus, and enhance student' academic engagement and performance. Ideas for incorporating creative movement into the school day (including activity breaks) are also included.